2005
DOI: 10.1359/jbmr.050114
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Receptor Fok1 Polymorphisms Affect Calcium Absorption, Kinetics, and Bone Mineralization Rates During Puberty

Abstract: Few studies of the VDR polymorphisms have looked at calcium metabolism or long-term effects. We measured bone mineralization and calcium metabolic parameters longitudinally in a group of 99 adolescents. We found a significant relationship between calcium absorption and skeletal calcium accretion and the Fok1, but not other VDR or related, genetic polymorphisms. It seems that the Fok1 polymorphism directly affects bone mineralization during pubertal growth through an effect on calcium absorption.Introduction: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
3
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(88 citation statements)
references
References 39 publications
6
74
3
5
Order By: Relevance
“…Vitamin D receptor Fok1 polymorphisms are significantly related to calcium absorption and whole body BMC in adolescents. (40) Race may be a crude indicator of genes that regulate body size, but habitual calcium intake and skin color may also be indicators in some cohorts.…”
Section: Barriers To Determining the Role Of Vitamin D Status On Skelmentioning
confidence: 99%
“…Vitamin D receptor Fok1 polymorphisms are significantly related to calcium absorption and whole body BMC in adolescents. (40) Race may be a crude indicator of genes that regulate body size, but habitual calcium intake and skin color may also be indicators in some cohorts.…”
Section: Barriers To Determining the Role Of Vitamin D Status On Skelmentioning
confidence: 99%
“…Moreover, Yu et al (42) indicated that Chinese women with the FF genotype regained more BMD after calcium supplementation. According to experimental studies, FOK1 can significantly affect the whole body BMD in those with a Ca intake.800 mg/d, while for those with a Ca intake800 mg/d, the FOK1 genotype did not have a significant effect on whole body BMD (43). Our evidence suggested that women with vitamin D intakes of less than 600 IU/d and the ff genotype had a higher total T-score and total Z-score, although, women with a vitamin D intake of more than the recommended dietary allowance (RDA.600 IU/d) and the FF genotype had a higher total T-score and total Z-score (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that BMD is not solely dependent upon genetic factors, but also upon environmental ones, such as calcium intake [23]. Results of studies on the matter are however somewhat conflicting.…”
Section: Discussionmentioning
confidence: 99%